Development of a new index of balance in adults with intellectual and developmental disabilities - Cuesta-Vargas, Antonio; Giné-Garriga, María (PLoS One, 2014)
Purposes: The first objective was to propose a new model representing the balance level of adults with intellectual and developmental disabilities (IDD) using Principal Components Analysis (PCA); and the second objective was to use the results from the PCA recorded by regression method to construct and validate summative scales of the standardized values of the index, which may be useful to facilitate a balance assessment in adults with IDD. Methods: A total of 801 individuals with IDD (509 males) mean 33.1 ± 8.5 years old, were recruited from Special Olympic Games in Spain 2009 to 2012. The participants performed the following tests: the timed-stand test, the single leg stance test with open and closed eyes, the Functional Reach Test, the Expanded Timed-Get-up-and-Go Test. Data was analyzed using principal components analysis (PCA) with Oblimin rotation and Kaiser normalization. We examined the construct validity of our proposed two-factor model underlying balance for adults with IDD. The scores from PCA were recorded by regression method and were standardized. Results: The Component Plot and Rotated Space indicated that a two-factor solution (Dynamic and Static Balance components) was optimal. The PCA with direct Oblimin rotation revealed a satisfactory percentage of total variance explained by the two factors: 51.6 and 21.4%, respectively. The median score standardized for component dynamic and static of the balance index for adults with IDD is shown how references values. Conclusions: Our study may lead to improvements in the understanding and assessment of balance in adults with IDD. First, it confirms that a two-factor model may underlie the balance construct, and second, it provides an index that may be useful for identifying the balance level for adults with IDD.
Keywords: Equilibrio (Fisiología); Minusválidos; Developmental Disabilities; Intellectual Disability; Postural Balance; Posture